2011
DOI: 10.4239/wjd.v2.i8.127
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind early life nutrition and adult disease outcome

Abstract: Obesity is increasing around the globe. While adult lifestyle factors undoubtedly contribute to the incidence of obesity and its attendant disorders, mounting evidence suggests that programming of obesity may occur following under- and over-nutrition during development. As hypothalamic control of appetite and energy expenditure is set early in life and can be perturbed by certain exposures such as undernutrition and altered metabolic and hormonal signals, in utero exposure to altered maternal nutrition and ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Compared with humans, rats showed a delay in brain development that involved lactation, as recently observed (Morgane et al 2002, Delahaye et al 2008. Therefore, this stage of life is particularly vulnerable to an energy metabolism imbalance when offspring reach adulthood (Velkoska & Morris 2011). Protein restriction early in life programs the adult metabolism toward several alterations through imprinting in the CNS (Resnick et al 1979) and in relation to the peripheral system/tissues, such as the hypothalamus-pituitary-adrenal (HPA) axis (Lesage et al 2006), skeletal muscle (Sampaio de Freitas et al 2003), liver (Ozanne 1999) and endocrine pancreas (Reusens & Remacle 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Compared with humans, rats showed a delay in brain development that involved lactation, as recently observed (Morgane et al 2002, Delahaye et al 2008. Therefore, this stage of life is particularly vulnerable to an energy metabolism imbalance when offspring reach adulthood (Velkoska & Morris 2011). Protein restriction early in life programs the adult metabolism toward several alterations through imprinting in the CNS (Resnick et al 1979) and in relation to the peripheral system/tissues, such as the hypothalamus-pituitary-adrenal (HPA) axis (Lesage et al 2006), skeletal muscle (Sampaio de Freitas et al 2003), liver (Ozanne 1999) and endocrine pancreas (Reusens & Remacle 2006).…”
Section: Introductionmentioning
confidence: 96%
“…The influences of early experiential perturbations have also been linked via both preclinical and clinical studies to an enhanced risk for the development of disease in adulthood . Early adversity is strongly implicated as one of the key determinants of risk for the development of psychiatric disorders such as anxiety and depression and perinatal nutritional perturbations have independently been demonstrated to contribute to the risk for diseases such as Type II diabetes and obesity . It is intriguing that several epidemiological studies have reported significant comorbidity between specific psychiatric disorders and metabolic dysfunction .…”
mentioning
confidence: 99%
“…9 Offspring of overnourished mothers have altered neuronal development, increased adiposity, and also exhibit hypertension, impaired cardiac function, and become hyperglycemic and hyperinsulinemic in adulthood. 10 Similar studies in rats have also demonstrated that mothers with a specifically high fat diet prior to conception and throughout pregnancy produce offspring with a similar metabolic syndrome phenotype in adulthood. 11 These studies highlight the importance of maternal diet in the During gestation, interactions between the mother and the fetus are critical for optimal growth and development.…”
Section: Prenatal Factors Maternal Nutritionmentioning
confidence: 69%